Drone warfare the development of unmanned aerial conflict - Sloggett, Dave (Pen & Sword Aviation, 2014)
The Development of Unmanned Aerial Conflict will examine the development and use of aerial drones, a topical subject that has not been written on to date. The book then looks at strategic uses of drones at present: Iran is being monitored; they are already in action over parts of Africa; what are other countries doing - China, Iran? Turkey? The RAF's use of drones, their deployment and operations is considered along with important questions such as where this goes for the future.